The MPO Forum for Malaysian Composers - Lena P.H. Lie (Wacana Seni Journal of Arts Discourse, 2003)
The concert saw six young Malaysian composers take center stage as the Malaysian Philharmonic Orchestra (MPO) ensemble (under the baton of Associate Conductor Mr. Kevin Field) premiered their six-minute compositions after aconsultation and mentoring session organized by the MPO. The concert hall was almost fully packed with avid art music followers who came to listen to the new works of the young composers who had strong music training at conservatoire of international standard.